An investigation on how brands in the mining sector can manage reputations in the context of the digital age: Harmony Gold - Molapo, Mahali (The IIE, 2017)
The digital age has made it easier to share and receive information through the World Wide Web, ultimately breaking geographical barriers. For most companies, this has increased the difficulty of reputation management as internet users mainly consumers increasingly find themselves in control of shared information and opinions about some companies and companies find themselves proportionately having less control over bad publicity posted on the internet. This can either lead to the success of a company or lead to erosion of a company’s reputation (Ott, 2013). This study will analyse how companies in the mining sector can manage reputations online using social media platform, Twitter. It questions how the South African gold mining company, Harmony Gold managed their reputation through Twitter in the last 3 months, during and following an illegal strike staged by 1,700 workers at their Kusasalethu mine in January 2017 (Africa News Agency, 2017). The mining industry is a very traditional one. A report generated by Deloitte based on tracking trends within the mining industry states that the need for mining companies to use social media is becoming increasingly important as it improves stakeholder engagement, enabling companies to communicate with their workers and bridge the gap between employees and management (Deloitte, 2016). An article by Mining Global, an international online mining magazine adds on to Deloitte’s appeal stating that mining companies have been known to avoid social media and public exposure with regards to their mining activities. (Mining Global, 2017). The goal of the study is to highlight the importance of online reputation management in a crisis and to explore how mining companies can adapt their online reputation management strategies in order to ultimately increase positive perceptions from the public and other stakeholders surrounding the industry. The study will make use of the interpretivism paradigm based on the assumption that “The social world does not exist independently of human knowledge.”(Maree, 2016). This paradigm plays a significant role in the study as the researcher investigates how reputations of companies within the mining sector are affected by the digital social world of Twitter and disciplines relating to how the social media platform is used by companies and stakeholders. This study will make use of a qualitative approach towards data collection whilst taking an ontological view on how the phenomenon of online reputation management came about. Harmony Gold’s recent strike concerning the payment of special bonuses at the company’s Kusasalethu mine (Eye Witness News, 2017), will be used as a case study. The study will 4 unobtrusively conduct a historical content analysis of the company’s Twitter page with the aim of understanding exactly how the company handled their online brand reputation through content creation on Twitter to address the crisis they faced as well as how this influenced the outcome with regards to relationship-driven elements of the adapted Octalysis tool by Jun Loayza on Reputation Hacks (2013).
Keywords: Mining Sector; Brands; Branding; Brand Reputation; Digital Communication; Social Media